Emotions in politics: a new approach to understanding political behavior - Hansen, Kristina Jessen (Politica, 2022)
Emotions are often seen as problematic in a democratic society where rationality should apparently rule. However, emotions are inevitable in politics, because politics is about people, and all human decision making is based on emotions. This article gives an introduction to research in emotions in politics, which is progressing rapidly. The article discusses what emotions are and gives an overview of the functions of specific emotions, e.g., anger, compassion and fear, as well as their consequences for political behavior. Finally, the article highlights six widespread misunderstandings and lists six principles for understanding the link between emotions and politics.